Second Language Chinese Computer‐Based Writing by Learners With Alphabetic First Languages: Writing Behaviors, Second Language Proficiency, Genre, and Text Quality. Issue 1 (7th September 2021) - Lu, Xiaojun
Abstract: This study examined the relationship of L2 Chinese proficiency with writing behaviors in L2 Chinese and whether this relationship is mediated by genre. It additionally investigated how writing behaviors relate to L2 Chinese text quality. A sample of 32 L2 writers of Chinese performed two argumentative and two narrative tasks on a computer. Their keystrokes were logged. Participants' L2 Chinese proficiency was estimated by a cloze test. Writing behaviors were operationalized as online measures of fluency, pausing, and revision. Text quality was assessed via holistic rating. Regression analyses revealed positive relationships of L2 proficiency to fluency, between‐word pause duration, between‐clause and between‐sentence pause frequency, and below‐clause revision frequency. L2 proficiency was also found to negatively correlate with within‐word and between‐word pause frequency and between‐sentence pause duration. Genre did not modulate the relationship of L2 proficiency to writing behaviors. More highly rated L2 Chinese texts were associated with fewer between‐word pauses. Abstract :